Rural medical workforce pathways: exploring the importance of postgraduation rural training time - Matthew R. McGrail; Tiana Gurney; Jordan Fox; Priya Martin; Diann Eley; Bushra Nasir; Srinivas Kondalsamy-Chennakesavan (BMC, 2023)
Abstract Background Inadequate distribution of the medical workforce in rural regions remains a key global challenge. Evidence of the importance of postgraduation (after medical school) rural immersion time and subsequent rural practice, particularly after accounting for other key factors, remains limited. This study investigated the combined impact of three key training pathway factors: (1) rural background, (2) medical school rural immersion, and (3) postgraduation rural immersion, and duration time of each immersion factor on working rurally. Methods Data from a cross-sectional national survey and a single university survey of Australian doctors who graduated between 2000 to 2018, were utilised. Key pathway factors were similarly measured. Postgraduation rural training time was both broad (first 10 years after medical school, national study) and specific (prevocational period, single university). This was firstly tested as the dependent variable (stage 1), then matched against rural practice (stage 2) amongst consultant doctors (national study, n = 1651) or vocational training doctors with consultants (single university, n = 478). Results Stage 1 modelling found rural background, > 1 year medical school rural training, being rural bonded, male and later choosing general practice were associated with spending a higher proportion (> 40%) of their postgraduation training time in a rural location. Stage 2 modelling revealed the dominant impact of postgraduation rural time on subsequent rural work for both General Practitioners (GPs) (OR 45, 95% CI 24 to 84) and other specialists (OR 11, 95% CI 5-22) based on the national dataset. Similar trends for both GPs (OR 3.8, 95% CI 1.6-9.1) and other specialists (OR 2.8, 95% CI 1.3-6.4) were observed based on prevocational time only (single university). Conclusions This study provides new evidence of the importance of postgraduation rural training time on subsequent rural practice, after accounting for key factors across the entire training pathway. It highlights that developing rural doctors aligns with two distinct career periods; stage 1-up to completing medical school; stage 2-after medical school. This evidence supports the need for strengthened rural training pathways after medical school, given its strong association with longer-term decisions to work rurally.